Analysis of refrigeration system working with nanolubricant - Mohd Hazwan Syafiq, Harun (2012)
Nanofluid is suspended of nanoparticles in a base fluid like water and lubricant oil with the purpose to increase rate of hate transfer either convection or conduction. It has been used in wide application such as in heat exchanger, automotive cooling and refrigeration system. The application of nanofluid in refrigeration system is a new approach with the purpose to increase rate of hate absorbed by evaporator. By increasing rate of heat absorbed in evaporator, the refrigeration system is able to cool down the refrigeration space faster than normal system. Currently, there are two types of approaches of nanofluid application in refrigeration system: 1) mixing with refrigerant and 2) mixing with refrigerant lubricant. Both of these approaches have no chose agreement each other and future research still in progress in this field. In order to find agreement between other researchers, this project has been conducted based on nanolubricant-refrigerant (called ‘nanolubricant’) approach. In this project Alumina and Carbon Nanotubes nanoparticles have been used in experiment. This two types of nanoparticles are selected based on study conducted by previous researchers who showed encouraging results. The nanolubricant is prepared by using 'two steps' technique which is alumina and CNT particles diluted with 'poly-ester lubricant' with concentration of 0.2%. There are three types of experiment have been conducted in this project. The first experiment is using normal lubricant which is ‘poly-ester’ lubricant, followed by experiments using CNT lubricant' and 'Alumina lubricant. The result shows that, with addition of nano particle into 'poly-ester lubricant' it increases the rate of refrigeration system performance. The maximum rate of performance improvement by adopting CNT into lubricant is 8.29%, while by using Alumina lubricant the maximum rate of performance improvement is 13.8%. As a calculation, Alumina is more suitable compared to CNT to be mixed with Ploy-ester lubricant for refrigeration system.